MINAT MASYARAKAT KOTA MEDAN TERHADAP PRODI ILMU HADIS FAKULTAS USHULUDDIN DAN STUDI ISLAM UIN SUMATERA UTARA - Syukri Syukri; Abdul Halim (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
“Science Study Hadith is a study that gives many opportunities for a person's response to deteriorate against him. Many opinions that people who take majors in hadith science study programs are people who do not have a clear and bright future, especially people whose life orientation only sees everything from the world glasses and sees that college is looking for work . This assumption arises because there is nothing that can be offered clearly about the work that is involved after the lecture process and becoming a graduate later, this is one of the factors that makes the interest of the city of Medan to the study program of the Hadith UIN North Sumatera is minimal. From this study there are several factors that influence the interest of the people of Medan to the study program of the Hadith of UIN North Sumatera, including location factors, social motive factors, emotional factors, and factors of encouragement or desire from self. To increase interest in the Study of Hadith, UIN North Sumatera offers several steps including conducting socialization in schools and the community, establishing cooperation, and improving the administration and quality of lecturers”